POD process wear-resistant plastic coating applied to keyboard and preparation method and application thereof

By optimizing the distribution ratio of the coating for POD process, the problem of poor acetone resistance in the prior art is solved, and the excellent performance of the coating on the keyboard surface is achieved, including solvent resistance and adhesion.

CN119752300APending Publication Date: 2025-04-04CASHEW MANFIELD (WUXI) INNOVATIVE MATERIALS LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993247.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to provide POD process coatings with good acetone resistance, especially in the field of 3C keyboards, resulting in poor performance of coatings when facing solvents such as acetone.

Method used

Improve the film forming, solvent resistance and adhesion of the coating by optimizing the composition ratio of UV white primer, PU black mid-paint and UV matte topcoat, including the use of specific polyurethane resins, reactive diluents and other additives.

Benefits of technology

It achieves excellent performance of the paint on the keyboard surface, including good acetone resistance, boiling resistance and adhesion, and meets the requirements of large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a POD process wear-resistant plastic coating applied to a keyboard, and a preparation method and application thereof, and belongs to the technical field of coatings. The POD process wear-resistant plastic coating of the present invention includes UV primer, PU intermediate paint, UV topcoat, acrylic resin, polyurethane resin, reactive diluent, etc., PU intermediate paint includes polyurethane resin, dispersant, etc., and UV topcoat includes UV polyurethane resin, acrylic resin, UV reactive diluent, etc. The present invention optimizes the components to prepare the POD process wear-resistant plastic coating, which can meet the industry standards for keyboard product production at home and abroad, has good decorative effect, low cost, simple construction, excellent quality assurance, and excellent solvent resistance; and while ensuring the stability of the coating performance, it has the advantage of good adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a POD process wear-resistant plastic coating applied to a keyboard, a preparation method thereof and an application thereof. Background Art

[0002] In recent years, with the satisfaction of material life, people pay more and more attention to the pursuit of spiritual level, and the use of smart devices has become more and more extensive, such as: smart phones, laptops, smart robots and other products; and coatings usually need to be coated on the surface of these products to make them beautiful, scratch-resistant, heat-resistant, sweat-resistant, solvent-resistant and other properties. The POD process (printing on demand technology) wear-resistant plastic coating for keyboard surface decoration is mainly used for the decoration and protection of the keyboard surface of laptop computers (hereinafter referred to as NB). Its general name is POD process wear-resistant plastic coating. With the development of the coating market economy, the competition in the coating industry is unprecedentedly fierce, and the market requirements for coatings are getting higher and higher. The development trend of world coatings is low pollution and high performance. Environmental protection has become a global issue. The coating industry must meet the requirements of the sustainable development strategy. The optimization and upgrading of the performance and process of coatings will become an inevitable trend. Therefore, it is necessary to develop POD process wear-resistant plastic coatings on keyboards.

[0003] In response to adjustments in the keyboard supply chain, it is very difficult to move the spray coating stage of the keyboard manufacturing process out of China in the short term (even if it is moved out, there will be a problem of low yield). Therefore, the POD (Production on Demand) process was created to complete the production of the customized part of the post-production stage according to the final order requirements; or ATO Assembly to Order, that is, to complete the development needs of the final production of keyboard coatings in the post-production stage according to the language included in the final order.

[0004] The POD process wear-resistant plastic coating used on keyboards is a kind of efficient, safe, healthy, high-performance, low-energy consumption coating, and its advantages are constantly emerging. Most of the 3C keyboard products on the market are laser engraved after spraying the color paint, and the acetone resistance is poor. How to prepare a coating suitable for the POD process and acetone resistance is the focus of research in this field. At present, both at home and abroad, the POD process wear-resistant plastic coating used on keyboards is still in the research and development and small-scale trial production stage. There are only a handful of manufacturers that can supply POD process wear-resistant plastic coatings used on keyboards, especially acetone-resistant UV white-bottom character primers. Currently, very few manufacturers have launched large-scale products in the field of 3C keyboards. How to provide a coating for the POD process with good acetone resistance is an urgent problem to be solved in this field. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a POD process wear-resistant plastic coating applied to a keyboard, and a preparation method and application thereof. The present invention optimizes the components to prepare a POD process wear-resistant plastic coating that can meet the industry standards for keyboard products at home and abroad, has good decorative effects, low costs, simple construction, excellent quality assurance, and excellent solvent resistance; and while ensuring the stability of the coating performance, it has the advantage of good adhesion.

[0006] The technical solution of the present invention is as follows: The first aspect of the present invention provides a POD process wear-resistant plastic coating applied to a keyboard, characterized in that it includes a UV primer, a PU intermediate paint, and a UV topcoat; The UV primer comprises the following raw materials in parts by weight: Acrylic resin 5-8 parts, polyurethane resin 25-35 parts, active diluent 9-11 parts, dispersant 1-1.2 parts, solvent I 7.5-13 parts, solvent II 2.5-5 parts, pigment 13-15 parts, anti-settling agent 2-3 parts, adhesion promoter 1-2 parts, filler 8-10 parts, matting powder 2.5-5.5 parts, photoinitiator 2.5-3 parts; The PU mid-coat comprises the following raw materials in parts by weight: Polyurethane resin 55-65 parts, dispersant 2-5 parts, solvent II 15-22 parts, pigment 3-5 parts, anti-settling agent 2-3 parts, wetting agent 0.2-0.3 parts, matting powder 4-5 parts; The UV topcoat comprises the following raw materials in parts by weight: 30-35 parts of UV polyurethane resin, 3-4 parts of acrylic resin, 6-8 parts of UV active diluent, 2.5-3 parts of photoinitiator, 3-5 parts of glass powder, 3.5-5 parts of solvent I; 6-10 parts of solvent II, 0.5-1 part of wetting agent, 0.5-1 part of leveling agent, 5-10 parts of anti-settling agent, 3-5 parts of wax powder, 1-5 parts of matting powder, and 15-20 parts of wax slurry.

[0007] The UV primer is a UV white primer; the PU intermediate paint is a PU black intermediate paint; and the UV topcoat is a UV matte topcoat.

[0008] In the UV primer, the acrylic resin includes Rohm and Haas A-11; the polyurethane resin is a UV polyurethane resin; the UV polyurethane resin consists of 6145-100 and 6215-100 of Changxing Chemical; the active diluent is a UV active diluent; the UV active diluent consists of EM265 and EM221 of Changxing Chemical.

[0009] In the UV primer, the dispersant includes EFKA-4310 from Ekawei; the solvent I includes methyl isobutyl ketone; the solvent II includes butyl acetate; the white pigment includes R902 from DuPont Chemical of the United States; the anti-settling agent includes NS-5500 from Disbaron; the adhesion promoter includes LTW from Germany's Sa; the filler includes talc; the matting powder includes E-1011 from Japan's Toso Co., Ltd.; and / or the photoinitiator includes photoinitiator 184 and photoinitiator TPO.

[0010] In the PU mid-coat, the polyurethane resin includes ESB-1205 from Dongsheng Chemical Company.

[0011] In the PU mid-coat, the dispersant includes EFKA-4310; The solvent II includes butyl acetate; the curing agent includes a mixture of HDI curing agent and butyl acetate, the mass ratio of the HDI curing agent to butyl acetate is 75:25; the HDI curing agent includes Bayer's N3390; The pigment is a black pigment; preferably, the black pigment includes Olironate 6 carbon black; The wetting agent includes BYK-358N from BYK; The matting powder includes E-1011 from Japan Toso Co., Ltd.

[0012] In the UV topcoat, the UV polyurethane resin includes 6145-100 from Changxing Chemical Company, 6071 from Changxing Chemical Company and L-6901 from Lancolu; the acrylic resin includes A-11 from Rohm and Haas; the UV active diluent includes EM265 from Changxing Chemical; and the photoinitiator includes photoinitiator 184 and TPO.

[0013] In the UV topcoat, the glass powder includes VX-SP of Japan Ronson Co., Ltd.; and / or, the solvent I includes methyl isobutyl ketone; the solvent II includes butyl acetate; the wetting agent includes BYK-358N of BYK; the leveling agent includes BYK-333 of BYK; the anti-settling agent includes NS-5500 of Disbaron; the wax powder includes Lanco TF1792 of Lubrizol; the matting powder includes E-1011 of Japan Toso Co., Ltd.; and the wax slurry includes ZJ-22 of Japan Gifu Co., Ltd.

[0014] The second aspect of the present invention provides a method for preparing the wear-resistant plastic coating using the POD process described in the first aspect, the method comprising the following steps: S1: Prepare UV primer, prepare each raw material according to the weight proportion of each raw material in UV primer, S1-1: Take 5-7.2 parts of solvent I, add 5-8 parts of acrylic resin while stirring at 300-500 rpm / min, then stir at 600-800 rpm / min to dissolve, add the remaining solvent I, and stir at 300-500 rpm / min for 10-15 minutes to obtain a semi-finished product 1-1; the fineness of the semi-finished product 1-1 is ≤10 μm; S1-2: 1-2.5 parts of solvent II, 1-1.2 parts of dispersant, and 5 parts of the semi-finished product 1-1 prepared in step S1-1 are mixed, and stirred at 300-500 rpm / min for 10-15 min; 13-15 parts of pigment are added, and stirred at 600-800 rpm / min until uniform, and then ground to a fineness of ≤20 μm, and then the remaining solvent II is added, and stirred at 300-500 rpm / min for 10-15 min to obtain a semi-finished product 1-2; the fineness of the semi-finished product 1-2 is ≤20 μm; S1-3: the remaining portions of the semi-finished product 1-1 of step S1-1, the semi-finished product 1-2 of step S1-2, 25-35 parts of polyurethane resin, and 9-11 parts of reactive diluent are mixed, and stirred at 300-500 rpm / min for 10-15 min, and then 8-10 parts of filler and 2.5-5.5 parts of matting powder are added in sequence, and stirred at 600-800 rpm / min for 20-30 min, and then 2.5-3 parts of photoinitiator, 2-3 parts of anti-settling agent, and 1-2 parts of adhesion promoter are added, and stirred at 500-600 rpm / min for 10-15 min to obtain a UV primer; S2: Prepare PU mid-coat, prepare each raw material according to the weight proportion of each raw material in PU mid-coat, S2-1: 11-13 parts of solvent II, 2-5 parts of dispersant, and 8-10 parts of polyurethane resin are mixed, stirred at 300-500 rpm / min for 10-15 min, 3-5 parts of pigment are added, and the mixture is stirred at 600-800 rpm / min until uniformly mixed, and then ground to a fineness of ≤20 μm, 2-3 parts of solvent II are added, and the mixture is stirred at 300-500 rpm / min for 10-15 min to obtain a semi-finished product 2-1, wherein the fineness of the semi-finished product 2-1 is ≤20 μm; S2-2: adding the remaining polyurethane resin to the semi-finished product 2-1 prepared in step S2-1, stirring at 300-500 rpm / min for 10-15 min, adding 4-5 parts of matting powder, stirring at 600-800 rpm / min for 20-30 min, adding 0.2-0.3 parts of wetting agent, 2-3 parts of anti-settling agent, and the remaining solvent II, and stirring at 300-500 rpm / min for 10-15 min to obtain PU intermediate paint; S3: Prepare UV topcoat, prepare each raw material according to the weight proportion of each raw material in the UV topcoat, S3-1: Add 3-4 parts of solvent I to 3-4 parts of acrylic resin while stirring at 300-500 rpm / min, then stir at 600-800 rpm / min to dissolve, add the remaining solvent I, stir at 300-500 rpm / min for 10-15 minutes to obtain a semi-finished product 3-1, wherein the fineness of the semi-finished product 3-1 is ≤10 μm; S3-2: 4-5.5 parts of solvent II, 30-35 parts of UV polyurethane resin, 6-8 parts of UV active diluent, and the semi-finished product 3-1 of step S1 are mixed, and stirred at 300-500rpm / min for 10-15min, and then 3-5 parts of glass powder, 3-5 parts of wax powder, and 1-5 parts of matting powder are added in sequence, and stirred at 600-800rpm / min for 20-30min, and then 2.5-3 parts of photoinitiator, 0.5-1 part of wetting agent, 0.5-1 part of leveling agent, 5-10 parts of anti-settling agent, 15-20 parts of wax slurry, and the remaining solvent II are added in sequence, and stirred at 300-500rpm / min for 10-15min to obtain a UV topcoat, wherein the fineness of the UV topcoat is ≤15μm.

[0015] The third aspect of the present invention provides an application of the wear-resistant plastic coating of the POD process described in the first aspect or the coating prepared by the preparation method described in the second aspect, wherein the coating is used to prepare a laser engraving coating on a keyboard, and a laser engraving product is obtained by laser engraving on the coating; The method of application is: (1) Prepare primer coating A, midcoat coating B, and topcoat coating C respectively; (2) coating the primer coating A of step (1) on the surface of the substrate, drying it, UV curing it, and cooling it to obtain a product containing a primer coating; (3) coating the surface of the product in step (2) with the intermediate coating B in step (1), drying, and cooling to obtain a product containing a primer coating and an intermediate coating; (4) continuing to coat the surface of the product in step (3) with the topcoat coating C in step (1), drying, UV curing, and cooling to obtain a product containing a primer coating, a midcoat coating, and a topcoat coating; (5) performing laser engraving on the product of step (4) to obtain a laser engraved product; In step (1), the coating A is obtained by mixing and stirring the UV primer, curing agent and diluent, and filtering; preferably, the mass ratio of the UV primer, curing agent and diluent is 100:5:70-90; And / or, the coating B is obtained by mixing and stirring the PU intermediate paint, curing agent and diluent, and filtering; the mass ratio of the PU intermediate paint, curing agent and diluent is 100:10:90-110; And / or, the coating C is obtained by mixing and stirring the UV coating and a diluent, and filtering; the mass ratio of the UV coating to the diluent is 100:60-80.

[0016] The beneficial technical effects of the present invention are: The present invention optimizes the components in UV white primer, UV black intermediate paint and UV matte topcoat, so that the coating obtained has better film-forming property, acetone resistance, water boiling resistance and excellent adhesion. Specifically, the polyurethane resin and active diluent in the UV white primer are used as film-forming substances, and have excellent adhesion, wear resistance, water boiling resistance and acetone resistance with the PC substrate; the polyurethane resin used in the UV black intermediate paint has excellent interlayer adhesion of the coating, and also has excellent chemical resistance, and high temperature and high humidity resistance; the polyurethane resin and active diluent in the matte topcoat can provide good adhesion, and also have excellent chemical resistance, high wear resistance, high hardness and easy laser engraving performance.

[0017] At the same time, the acrylic resin, polyurethane resin and pigment used can obtain good grindability and color development under the action of dispersant, greatly improving the covering performance of the coating; the wetting agent and leveling agent, due to its unique silicone chemical structure, can reduce the surface tension of the coating in the wet film state, and at the same time play a dispersing and stabilizing role in the wetting of the filler, and can produce coating products with better fineness at a lower stirring speed.

[0018] The present invention further limits the type of polyurethane resin used, the type or parameter of raw materials such as active diluent, and optimizes the performance of the slurry.

[0019] The preparation method of the POD process wear-resistant plastic coating of the present invention is simple and easy to operate. At the same time, the coating prepared by the coating has excellent acetone resistance, realizes the process of spraying UV primer, UV intermediate paint, UV topcoat and then laser engraving characters, and can meet the acetone resistance, wear resistance and other properties of the characters after laser engraving, and can fully meet the requirements of large-scale industrial production. DETAILED DESCRIPTION

[0020] The present invention will be described in detail below in conjunction with the embodiments.

[0021] The present invention provides a POD process wear-resistant plastic coating applied to a keyboard, and defines the model and ratio of UV polyurethane resin and UV active diluent in the primer used. The UV polyurethane resin used in the present invention is UV polyurethane resin 6145-100 and 6215-100; the UV active diluent used is UV active diluent EM265 and UV active diluent EM221. The polyurethane resin and active diluent used as main film-forming materials have excellent adhesion to PC substrate, wear resistance, water boiling resistance, and acetone resistance. The polyurethane resins 6145-100 and 6215-100 used have the characteristics of good adhesion, fast reaction, chemical resistance, wear resistance, acetone solvent resistance, water boiling resistance, etc., and the chemical resistance, wear resistance, acetone solvent resistance, water boiling resistance, etc. are improved by adjusting their ratios. The combination of UV active diluent EM265 and UV active diluent EM221 can increase the crosslinking density of the coating, thereby improving the chemical resistance, wear resistance, acetone solvent resistance, boiling water resistance and other properties of the paint film. It can be understood that in the present invention, the polyurethane resin EBS-1205 used in the mid-coat is the main film-forming material, the coating has excellent interlayer adhesion, and is resistant to chemicals, high temperature and high humidity. The UV polyurethane resin 6145-100, UV polyurethane resin 6071, UV polyurethane resin L-6901, and UV active diluent EM265 in the topcoat are the main film-forming materials, and the coating has excellent interlayer adhesion, chemical resistance, wear resistance, hardness, and easy laser carving.

[0022] It can be understood that in the present invention, acrylic resin A-11, polyurethane resin ESB-1205 and pigment can obtain good grindability and color development under the action of dispersant, greatly improving the covering performance of coating; wetting agent and leveling agent, due to their unique organosilicon chemical structure, can reduce the surface tension of coating in wet film state, and at the same time play a dispersing and stabilizing role in the wetting of filler, and can produce coating products with better fineness at a lower stirring speed.

[0023] It is understandable that the glass powder VX-SP and wax powder TF1792 used in the present invention can improve the surface hardness of the paint film, thereby improving the wear resistance of pencils, wool felt and the like.

[0024] The present invention will be further described below by way of examples and the like.

[0025] Example 1 A POD process wear-resistant plastic coating used on a keyboard, comprising a UV white primer, a PU black intermediate paint, and a UV matte topcoat.

[0026] The raw materials and their weight proportions in the UV white primer, PU black mid-coat and UV matte topcoat are as shown in the preparation method.

[0027] The preparation method of the POD process wear-resistant plastic coating applied to the keyboard comprises the following steps: UV white primer preparation: (1) Take a reaction tank, add 7.2 parts of methyl isobutyl ketone, start stirring, and add 5.8 parts of A-11 acrylic resin from Rohm and Haas Company in sequence at a stirring speed of 300 rpm / min. After adding, stir and dissolve at a stirring speed of 600 rpm / min until it becomes a clear and transparent liquid. Then add 4 parts of methyl isobutyl ketone, and stir at a stirring speed of 300 rpm / min for 15 minutes until it is evenly mixed. The standard for even mixing is that the detection fineness is ≦10 μm, and a semi-finished product is obtained; (2) Take another reaction cylinder, add 1.5 parts of butyl acetate, 2 parts of dispersant EFKA-4310, and 5 parts of the semi-finished product obtained in step 1, start stirring, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed. Under stirring, add 15 parts of DuPont R902 titanium dioxide (pigment) in sequence. After adding, stir at a stirring speed of 600 rpm / min until the mixture is uniformly mixed, grind to a fineness of ≦20 μm, then add 1.5 parts of butyl acetate, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed. The standard for uniform mixing is a detection fineness of ≦20 μm, and obtain a semi-finished product; (3) Take another reaction tank, add 12 parts of the semi-finished product obtained in step (1), 25 parts of the semi-finished product obtained in step (2), 25 parts of 6145-100 polyurethane resin, 7.5 parts of 6215-100 polyurethane resin, 7.5 parts of active diluent EM265 and 2.5 parts of EM221 from Changxing Chemical Company, start stirring, and stir at a stirring speed of 300 rpm / min for 12 minutes until the mixture is uniformly mixed; while continuing to stir, add 8.5 parts of talcum powder and 5 parts of matting powder E-1011 from Dongcao in sequence, and after adding them, stir at a stirring speed of 600 rpm / min for 25 minutes until the mixture is uniformly mixed, and then add 2 parts of photoinitiator 184 and 0.5 parts of TPO from Double Bond Company, 3 parts of anti-settling agent NS-5500, and adhesion promoter LTW in sequence. 1.5 parts, stir at a stirring speed of 600 rpm / min for 15 minutes until the mixture is uniform, to obtain a finished coating, which can be prepared with the curing agent before use.

[0028] PU black mid-coat preparation: (1) Take a reaction tank, add 12 parts of butyl acetate, 2.25 parts of dispersant EFKA-4310, and 9 parts of ESB-1205 polyurethane resin from Dongsheng Chemical Company, stir for 15 minutes at a stirring speed of 300 rpm / min until the mixture is uniformly mixed, add 4.5 parts of pigment Olilonte 6 carbon black in sequence under stirring, stir at a stirring speed of 600 rpm / min until the mixture is uniformly mixed, grind to a fineness of ≦20 um, add 2.25 parts of butyl acetate, stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed, and the standard for the uniform mixing is a detection fineness of ≦20 μm, to obtain a semi-finished product; (2) Take another reaction tank, add 55 parts of ESB-1205 polyurethane resin produced by Dongsheng Chemical Company, add 30 parts of the semi-finished product obtained in step (1), start stirring, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed; under stirring, add 5 parts of matting powder E-1011 produced by Dongtan in sequence, after adding, stir at a stirring speed of 600 rpm / min for 20 minutes until the mixture is uniformly mixed, then add 0.3 parts of wetting agent BYK-358N, 3 parts of anti-settling agent NS-5500, and 6.7 parts of butyl acetate in sequence, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed to obtain a finished coating, which is prepared with a curing agent when used.

[0029] UV matte topcoat preparation: (1) Take a reaction tank, add 3.5 parts of methyl isobutyl ketone, start stirring, and add 3 parts of A-11 acrylic resin from Rohm and Haas Company in sequence at a stirring speed of 300 rpm / min. After adding, stir and dissolve at a stirring speed of 600 rpm / min until it becomes a clear and transparent liquid. Then add 1 part of methyl isobutyl ketone and stir at a stirring speed of 300 rpm / min for 15 minutes until it is evenly mixed. The standard for even mixing is that the test fineness is ≦10μm, and a semi-finished product is obtained; (2) Take a reaction tank, add 5 parts of butyl acetate, 7.5 parts of the semi-finished product obtained in step (1), 18.5 parts of 6145-100 polyurethane resin from Changxing Chemical Company, 7 parts of polyurethane resin 6071, 7 parts of L-6901 polyurethane resin from Lancolu Company and 7 parts of EM265 UV active diluent, start stirring, and stir at a stirring speed of 300 rpm / min for 12 minutes until the mixture is uniformly mixed; while continuing to stir, add 5 parts of glass powder from Longsen Company, 5 parts of wax powder TF1792 from Lubrizol Company and 1.5 parts of matting powder E-1011 from Dongcao in sequence, and after adding, stir at a stirring speed of 600 rpm / min for 20-30 minutes until the mixture is uniformly mixed, and then add 2.5 parts of photoinitiator 184 and 0.3 parts of TPO from Double Bond Company, 10 parts of anti-settling agent NS-5500 and 1.5 parts of leveling agent BYK-333 from Double Bond Company in sequence. 0.5 parts of butyl acetate, 0.5 parts of wetting agent BYK-358N, 20 parts of wax paste ZJ-22 produced by Gifu Company, and 3.2 parts of butyl acetate were stirred at a stirring speed of 600 rpm / min for 15 minutes until the mixture was uniform, thereby obtaining a finished coating.

[0030] Example 2 A POD process wear-resistant plastic coating used on a keyboard, comprising a UV white primer, a PU black intermediate paint, and a UV matte topcoat.

[0031] The raw materials and their weight proportions in the UV white primer, PU black mid-coat and UV matte topcoat are as shown in the preparation method.

[0032] The preparation method of the POD process wear-resistant plastic coating applied to the keyboard comprises the following steps: UV white primer preparation: (1) Take a reaction tank, add 7.2 parts of methyl isobutyl ketone, start stirring, and add 5.8 parts of A-11 acrylic resin from Rohm and Haas Company in sequence at a stirring speed of 300 rpm / min. After adding, stir and dissolve at a stirring speed of 600 rpm / min until it becomes a clear and transparent liquid. Then add 4 parts of methyl isobutyl ketone and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed. The standard for uniform mixing is that the detection fineness is ≦10 μm, and a semi-finished product is obtained; (2) Take another reaction cylinder, add 1.5 parts of butyl acetate, 2 parts of dispersant EFKA-4310, and 5 parts of the semi-finished product obtained in step 1, start stirring, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed. Under stirring, add 15 parts of DuPont R902 titanium dioxide (pigment) in sequence. After adding, stir at a stirring speed of 600 rpm / min until the mixture is uniformly mixed, grind to a fineness of ≦20 μm, then add 1.5 parts of butyl acetate, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed. The standard for uniform mixing is a detection fineness of ≦20 μm, and obtain a semi-finished product; (3) Take another reaction tank, add 12 parts of the semi-finished product obtained in step (1), 25 parts of the semi-finished product obtained in step (2), 20 parts of 6145-100 polyurethane resin, 12.5 parts of 6215-100 polyurethane resin, 7.5 parts of EM265 active diluent and 2.5 parts of EM221 active diluent from Changxing Chemical Company, start stirring, and stir at a stirring speed of 300 rpm / min for 12 minutes until the mixture is uniformly mixed; while continuing to stir, add 8.5 parts of talcum powder and 5 parts of matting powder E-1011 from Dongcao in sequence, and after adding them, stir at a stirring speed of 600 rpm / min for 25 minutes until the mixture is uniformly mixed, and then add 2 parts of photoinitiator 184 and 0.5 parts of TPO from Double Bond Company, 3 parts of anti-settling agent NS-5500, and adhesion promoter LTW in sequence. 1.5 parts, stir at a stirring speed of 600 rpm / min for 15 minutes until the mixture is uniform, to obtain a finished coating, which can be prepared with the curing agent before use.

[0033] PU black mid-coat preparation: (1) Take a reaction tank, add 12 parts of butyl acetate, 2.25 parts of dispersant EFKA-4310, and 9 parts of ESB-1205 polyurethane resin from Dongsheng Chemical Company, stir for 15 minutes at a stirring speed of 300 rpm / min until the mixture is evenly mixed, then add 4.5 parts of pigment Olilonte 6 carbon black in sequence under stirring, stir at a stirring speed of 600 rpm / min until the mixture is evenly mixed, grind to a fineness of ≦20 um, then add 2.25 parts of butyl acetate, stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is evenly mixed, and the standard for the even mixing is a detection fineness of ≦20 μm, to obtain a semi-finished product; (2) Take another reaction tank, add 55 parts of ESB-1205 polyurethane resin produced by Dongsheng Chemical Company, add 30 parts of the semi-finished product obtained in step (1), start stirring, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed; under stirring, add 5 parts of matting powder E-1011 produced by Dongtan in sequence, after adding, stir at a stirring speed of 600 rpm / min for 20 minutes until the mixture is uniformly mixed, then add 0.3 parts of wetting agent BYK-358N, 3 parts of anti-settling agent NS-5500, and 6.7 parts of butyl acetate in sequence, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed to obtain a finished coating, which is prepared with a curing agent when used.

[0034] UV matte topcoat preparation: (1) Take a reaction tank, add 3.5 parts of methyl isobutyl ketone, start stirring, and add 3 parts of A-11 acrylic resin from Rohm and Haas Company in sequence at a stirring speed of 300 rpm / min. After adding, stir and dissolve at a stirring speed of 600 rpm / min until it becomes a clear and transparent liquid. Then add 1 part of methyl isobutyl ketone and stir at a stirring speed of 300 rpm / min for 15 minutes until it is evenly mixed. The standard for even mixing is that the test fineness is ≦10μm, and a semi-finished product is obtained; (2) Take a reaction tank, add 5 parts of butyl acetate, 7.5 parts of the semi-finished product obtained in step (1), 18.5 parts of 6145-100 polyurethane resin from Changxing Chemical Company, 7 parts of 6071 polyurethane resin, 7 parts of L-6901 polyurethane resin from Lancolu Company and 7 parts of EM265UV active diluent, start stirring, and stir at a stirring speed of 300 rpm / min for 12 minutes until the mixture is uniformly mixed; while continuing to stir, add 5 parts of glass powder from Longsen Company, 5 parts of wax powder TF1792 from Lubrizol Company and 1.5 parts of matting powder E-1011 from Dongcao in sequence, and after adding, stir at a stirring speed of 600 rpm / min for 20-30 minutes until the mixture is uniformly mixed, and then add 2.5 parts of photoinitiator 184 and 0.3 parts of TPO from Double Bond Company, 10 parts of anti-settling agent NS-5500 and 1.5 parts of leveling agent BYK-333 from Double Bond Company in sequence. 0.5 parts of butyl acetate, 0.5 parts of wetting agent BYK-358N, 20 parts of wax paste ZJ-22 produced by Gifu Company, and 3.2 parts of butyl acetate were stirred at a stirring speed of 600 rpm / min for 15 minutes until the mixture was uniform, thereby obtaining a finished coating.

[0035] Comparative Example 1 A POD process wear-resistant plastic coating used on a keyboard, comprising a UV white primer, a PU black intermediate paint, and a UV matte topcoat.

[0036] Among them, the weight proportions of each raw material in UV white primer, PU black mid-coat and UV matte topcoat can be seen in the preparation method.

[0037] The preparation method of the POD process wear-resistant plastic coating applied to the keyboard comprises the following steps: UV white primer preparation: (1) Take a reaction tank, add 7.2 parts of methyl isobutyl ketone, start stirring, and add 5.8 parts of A-11 from Rohm and Haas at a stirring speed of 300 rpm / min. After adding, stir and dissolve at a stirring speed of 600 rpm / min until it becomes a clear and transparent liquid. Then add 4 parts of methyl isobutyl ketone and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is evenly mixed. The standard for even mixing is that the detection fineness is ≦10 μm, and a semi-finished product is obtained; (2) Take another reaction cylinder, add 1.5 parts of butyl acetate, 2 parts of dispersant EFKA-4310, and 5 parts of the semi-finished product obtained in step 1, start stirring, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is evenly mixed. Under stirring, add 15 parts of DuPont R902 titanium dioxide (pigment) in sequence. After adding, stir at a stirring speed of 600 rpm / min until the mixture is evenly mixed, grind to a fineness of ≦20 μm, then add 1.5 parts of butyl acetate, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is evenly mixed. The standard for even mixing is a detection fineness of ≦20 μm, and obtain a semi-finished product; (3) Take another reaction tank, add 12 parts of the semi-finished product obtained in step (1), 25 parts of the semi-finished product obtained in step (2), 7.5 parts of 6145-100 polyurethane resin, 25 parts of 6215-100 polyurethane resin, and 10 parts of EM265 active diluent from Changxing Chemical Company, and start stirring. Stir for 12 minutes at a stirring speed of 300 rpm / min until the mixture is uniformly mixed. While continuing to stir, add 8.5 parts of talcum powder and 5 parts of matting powder E-1011 from Dongcao in sequence. After adding, stir for 25 minutes at a stirring speed of 600 rpm / min until the mixture is uniformly mixed. Then, add 2 parts of photoinitiator 184 and 0.5 parts of TPO, 3 parts of anti-settling agent NS-5500, and 1.5 parts of adhesion promoter LTW from Shuangbang Company in sequence. Stir for 15 minutes at a stirring speed of 600 rpm / min until the mixture is uniformly mixed. A finished coating is obtained, which is prepared with a curing agent when used.

[0038] PU black mid-coat preparation: (1) Take a reaction tank, add 12 parts of butyl acetate, 2.25 parts of dispersant EFKA-4310, and 9 parts of ESB-1205 polyurethane resin from Dongsheng Chemical Company, stir for 15 minutes at a stirring speed of 300 rpm / min until the mixture is uniformly mixed, add 4.5 parts of pigment Olilonte 6 carbon black in sequence under stirring, stir at a stirring speed of 600 rpm / min until the mixture is uniformly mixed, grind to a fineness of ≦20 um, add 2.25 parts of butyl acetate, stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed, and the standard for the uniform mixing is a detection fineness of ≦20 μm, to obtain a semi-finished product; (2) Take another reaction tank, add 55 parts of ESB-1205 polyurethane resin produced by Dongsheng Chemical Company, add 30 parts of the semi-finished product obtained in step (1), start stirring, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed; under stirring, add 5 parts of matting powder E-1011 produced by Dongtan in sequence, after adding, stir at a stirring speed of 600 rpm / min for 20 minutes until the mixture is uniformly mixed, then add 0.3 parts of wetting agent BYK-358N, 3 parts of anti-settling agent NS-5500, and 6.7 parts of butyl acetate in sequence, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed to obtain a finished coating, which is prepared with a curing agent when used.

[0039] UV matte topcoat preparation: (1) Take a reaction tank, add 3.5 parts of methyl isobutyl ketone, start stirring, and add 3 parts of A-11 acrylic resin from Rohm and Haas Company in sequence at a stirring speed of 300 rpm / min. After adding, stir and dissolve at a stirring speed of 600 rpm / min until it becomes a clear and transparent liquid. Then add 1 part of methyl isobutyl ketone and stir at a stirring speed of 300 rpm / min for 15 minutes until it is evenly mixed. The standard for even mixing is that the test fineness is ≦10μm, and a semi-finished product is obtained; (2) Take a reaction tank, add 5 parts of butyl acetate, 7.5 parts of the semi-finished product obtained in step (1), 18.5 parts of 6145-100 polyurethane resin from Changxing Chemical Company, 7 parts of 6071 polyurethane resin, 7 parts of L-6901 polyurethane resin from Lancolu Company and 7 parts of EM265UV active diluent, start stirring, and stir at a stirring speed of 300 rpm / min for 12 minutes until the mixture is uniformly mixed; while continuing to stir, add 5 parts of glass powder from Longsen Company, 5 parts of wax powder TF1792 from Lubrizol Company and 1.5 parts of matting powder E-1011 from Dongcao in sequence, and after adding, stir at a stirring speed of 600 rpm / min for 20-30 minutes until the mixture is uniformly mixed, and then add 2.5 parts of photoinitiator 184 and 0.3 parts of TPO from Double Bond Company, 10 parts of anti-settling agent NS-5500 and 1.5 parts of leveling agent BYK-333 from Double Bond Company in sequence. 0.5 parts of butyl acetate, 0.5 parts of wetting agent BYK-358N, 20 parts of wax paste ZJ-22 produced by Gifu Company, and 3.2 parts of butyl acetate were stirred at a stirring speed of 600 rpm / min for 15 minutes until the mixture was uniform, thereby obtaining a finished coating.

[0040] Comparative Example 2 A POD process wear-resistant plastic coating used on a keyboard, comprising a UV white primer, a PU black intermediate paint, and a UV matte topcoat.

[0041] Among them, the weight proportions of each raw material in UV white primer, PU black mid-coat and UV matte topcoat can be seen in the preparation method.

[0042] The preparation method of the POD process wear-resistant plastic coating applied to the keyboard comprises the following steps: UV white primer preparation: (1) Take a reaction tank, add 7.2 parts of methyl isobutyl ketone, start stirring, and add 5.8 parts of A-11 acrylic resin from Rohm and Haas Company in sequence at a stirring speed of 300 rpm / min. After adding, stir and dissolve at a stirring speed of 600 rpm / min until it becomes a clear and transparent liquid. Then add 4 parts of methyl isobutyl ketone and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed. The standard for uniform mixing is that the detection fineness is ≦10 μm, and a semi-finished product is obtained; (2) Take another reaction cylinder, add 1.5 parts of butyl acetate, 2 parts of dispersant EFKA-4310, and 5 parts of the semi-finished product obtained in step 1, start stirring, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is evenly mixed. Under stirring, add 15 parts of DuPont R902 titanium dioxide (pigment) in sequence. After adding, stir at a stirring speed of 600 rpm / min until the mixture is evenly mixed, grind to a fineness of ≦20 μm, then add 1.5 parts of butyl acetate, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is evenly mixed. The standard for even mixing is a detection fineness of ≦20 μm, and obtain a semi-finished product; (3) Take another reaction tank, add 12 parts of the semi-finished product obtained in step (1), 25 parts of the semi-finished product obtained in step (2), 16.5 parts of 6145-100 polyurethane resin, 16 parts of 6215-100 polyurethane resin, 7.5 parts of EM265 active diluent and 2.5 parts of EM221 active diluent from Changxing Chemical Company, start stirring, and stir at a stirring speed of 300 rpm / min for 12 minutes until the mixture is uniformly mixed; while continuing to stir, add 8.5 parts of talcum powder and 5 parts of matting powder E-1011 from Dongcao in sequence, and after adding them, stir at a stirring speed of 600 rpm / min for 25 minutes until the mixture is uniformly mixed, and then add 2 parts of photoinitiator 184 and 0.5 parts of TPO from Double Bond Company, 3 parts of anti-settling agent NS-5500, and adhesion promoter LTW in sequence. 1.5 parts, stir at a stirring speed of 600 rpm / min for 15 minutes until the mixture is uniform, to obtain a finished coating, which can be prepared with the curing agent before use.

[0043] PU black mid-coat preparation: (1) Take a reaction tank, add 12 parts of butyl acetate, 2.25 parts of dispersant EFKA-4310, and 9 parts of ESB-1205 polyurethane resin from Dongsheng Chemical Company, stir for 15 minutes at a stirring speed of 300 rpm / min until the mixture is uniformly mixed, add 4.5 parts of pigment Olilonte 6 carbon black in sequence under stirring, stir at a stirring speed of 600 rpm / min until the mixture is uniformly mixed, grind to a fineness of ≦20 um, add 2.25 parts of butyl acetate, stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed, and the standard for the uniform mixing is a detection fineness of ≦20 μm, to obtain a semi-finished product; (2) Take another reaction tank, add 55 parts of ESB-1205 polyurethane resin produced by Dongsheng Chemical Company, add 30 parts of the semi-finished product obtained in step (1), start stirring, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed; under stirring, add 5 parts of matting powder E-1011 produced by Dongtan in sequence, after adding, stir at a stirring speed of 600 rpm / min for 20 minutes until the mixture is uniformly mixed, then add 0.3 parts of wetting agent BYK-358N, 3 parts of anti-settling agent NS-5500, and 6.7 parts of butyl acetate in sequence, and stir at a stirring speed of 300 rpm / min for 15 minutes until the mixture is uniformly mixed to obtain a finished coating, which is prepared with a curing agent when used.

[0044] UV matte topcoat preparation: (1) Take a reaction tank, add 3.5 parts of methyl isobutyl ketone, start stirring, and add 3 parts of A-11 acrylic resin from Rohm and Haas Company in sequence at a stirring speed of 300 rpm / min. After adding, stir and dissolve at a stirring speed of 600 rpm / min until it becomes a clear and transparent liquid. Then add 1 part of methyl isobutyl ketone and stir at a stirring speed of 300 rpm / min for 15 minutes until it is evenly mixed. The standard for even mixing is that the test fineness is ≦10μm, and a semi-finished product is obtained; (2) Take a reaction tank, add 5 parts of butyl acetate, 7.5 parts of the semi-finished product obtained in step (1), 18.5 parts of 6145-100 polyurethane resin from Changxing Chemical Company, 7 parts of 6071 polyurethane resin, 7 parts of L-6901 polyurethane resin from Lancolu Company and 7 parts of EM265UV active diluent, start stirring, and stir for 12 minutes at a stirring speed of 300 rpm / min until the mixture is uniformly mixed; while continuing to stir, add 5 parts of glass powder from Longsen Company, 5 parts of wax powder TF1792 from Lubrizol Company and 1.5 parts of matting powder E-1011 from Dongcao in sequence, and after adding, stir for 20-30 minutes at a stirring speed of 600 rpm / min until the mixture is uniformly mixed, and then add 2.5 parts of photoinitiator 184 and 0.3 parts of TPO from Double Bond Company, 10 parts of anti-settling agent NS-5500 and 1.5 parts of leveling agent BYK-333 from Double Bond Company in sequence. 0.5 parts of butyl acetate, 0.5 parts of wetting agent BYK-358N, 20 parts of wax paste ZJ-22 produced by Gifu Company, and 3.2 parts of butyl acetate were stirred at a stirring speed of 600 rpm / min for 15 minutes until the mixture was uniform, thereby obtaining a finished coating.

[0045] Comparative Example 3 A POD process wear-resistant plastic coating used on a keyboard, the components, proportions and preparation method of which are basically the same as those of Example 1, except that the ratio of two polyurethane resins in the UV white primer is changed in this comparative example. In this comparative example, 27 parts of 6145-100 polyurethane resin and 5.5 parts of 6215-100 polyurethane resin from Changxing Chemical Company are used.

[0046] Comparative Example 4 A POD process wear-resistant plastic coating used on a keyboard, the components, proportions and preparation method of which are basically the same as those of Example 1, except that the ratio of two polyurethane resins in the UV white primer is changed in this comparative example. In this comparative example, 5.5 parts of 6145-100 polyurethane resin and 27 parts of 6215-100 polyurethane resin from Changxing Chemical Company are used.

[0047] Application Example 1-2 The POD process wear-resistant plastic coating obtained in Examples 1-2 was coated on the PC transparent key material respectively, and the coating process was as follows: The primer: curing agent: diluent = 100: 5: 80, stirred at a low speed of 300 rpm for 5 minutes, and filtered through 300 mesh to obtain coating A; the middle paint: curing agent: diluent = 100: 10: 100, stirred at a low speed of 300 rpm for 5 minutes, and filtered through 300 mesh to obtain coating B; The topcoat: thinner ratio was 100:70, stirred at a low speed of 300 rpm for 5 minutes, and then filtered through 300 mesh to obtain coating C; The above diluent is a mixture of butyl acetate, ethyl acetate, anti-white water and benzophenone alcohol in a mass ratio of 60:22:15:3; (2) The coating A obtained in step (1) is sprayed onto the product in a clean room. The temperature of the clean room is controlled at 25-30°C, the humidity is controlled at 50-70%, the spraying air pressure is 0.3MPa, and the dry film thickness is controlled at 10-14μm. The sprayed product is placed in an oven at 50°C for 7 minutes and UV curing is performed at an energy of 700mj / cm 2 , power is 100mw / cm 2 , after cooling, wait for spraying middle coating; (3) spraying the coating B obtained in step (1) onto the product obtained in step (2) in a clean room, wherein the temperature of the clean room is controlled at 25-30°C, the humidity is controlled at 50-70%, the spraying air pressure is 0.3 MPa, and the dry film thickness is controlled at 16-20 μm; (4) Place the product sprayed in step (3) in an oven, set the temperature to 60 degrees Celsius, and place it for 2 hours. After cooling, spray the UV top coating.

[0048] (5) The coating C obtained in step (1) is sprayed onto the product obtained in step (3) in a clean room. The temperature of the clean room is controlled at 25-30°C, the humidity is controlled at 50-70%, the spraying air pressure is 0.3MPa, and the dry film thickness is controlled at 13-17μm. The sprayed product is placed in an oven at 50°C for 7 minutes and UV curing is performed at an energy of 700mj / cm 2 , power is 100mw / cm 2 After cooling, a sample containing a layer is obtained, and then the required language characters are laser engraved to obtain a final sample containing characters.

[0049] When conducting performance tests, the final sample must be baked at 60°C for 2 hours and then cooled before testing.

[0050] Comparative Application Examples 1-4 The POD process wear-resistant plastic coatings obtained in Comparative Examples 1-4 were coated on PC transparent key materials respectively. The coating process was basically the same as that of Application Examples 1-2, except that the coatings used were the coatings prepared in Comparative Examples 1-4.

[0051] Test example: The final samples of the application examples and comparative application examples of the present invention were subjected to performance tests. The detection methods were all standard methods. The adhesion of the transparent PC key was tested according to the standard GB / T 9286-1998; the chemical resistance was tested according to the standard GB / T 1735-2009: SPF 30 protection / 65°C, 95%, 72h. The high temperature and high humidity resistance was measured according to the standard GB / T 1735-2009: 65°C, 95%, 72h. The RCA wear resistance was measured according to the standard ASTM F2357, and the conditions were: 175g, ≧250 times. The pencil hardness was measured according to the standard GB / T6379-199, and the conditions were: 500g load for 2H. The CS-10F rubber wear test was measured according to the standard GB / T 23989-2009, and the conditions were: 500g load, ≧300 times. The test of covering the laser engraved character position with acetone cotton cloth passed the sensory test, and observed whether there was obvious imprint on the appearance. If not, record no change, if yes, record character wrinkles. 95% alcohol abrasion test was conducted according to standard GB / T 23989-2009, and the conditions were: 500g load, ≧100 times. Boiling performance test was conducted according to standard ASTM D870, and the conditions were: 60℃*3h. 5% salt spray performance test was conducted according to standard GB6458-86, and the conditions were: 72 hours. CS-5 wool felt abrasion test was conducted according to standard GB / T 23989-2009, and the conditions were: 200g load, ≧25W times, and the gloss change was ≦3 degrees. Pencil abrasion test was conducted according to standard GB / T 23989-2009, and the test conditions were: 500g load, 10W times, and the gloss change was ≦10 degrees. The test results are shown in Table 1.

[0052] Table 1: Performance tests of corresponding coatings of Examples and Comparative Examples

[0053] From the results in the above table, it can be seen that the coating obtained in Comparative Example 1-2 has good adhesion on the PC transparent key material, and has good performance in chemical resistance, high temperature and humidity resistance, wear resistance, hardness, water boiling resistance, salt spray resistance, etc., but the acetone cotton cloth covering test of the laser engraved character position after UV topcoat will wrinkle; the coating obtained in Comparative Example 3 has decreased adhesion, high temperature and humidity resistance, and water boiling resistance on the PC transparent key material, but has good performance in chemical resistance, wear resistance, hardness, salt spray resistance, etc., and the acetone cotton cloth covering test of the laser engraved character position after UV topcoat also shows good performance; The coating obtained in proportion 4 has good adhesion on the PC transparent key material, and has good performance in chemical resistance, high temperature and humidity resistance, wear resistance, hardness, boiling resistance, salt spray resistance, etc. However, the acetone cotton cloth covering test at the laser engraved character position after UV topcoat will wrinkle and peel off; the coating obtained in Example 1-2 not only has good adhesion, but also has the advantages of chemical resistance, high temperature resistance, humidity resistance, wear resistance, boiling resistance, salt spray resistance, high hardness, etc. At the same time, the acetone cotton cloth covering test at the laser engraved character position after UV topcoat will not wrinkle at all, and the supporting performance of the coating can fully meet the requirements.

[0054] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. The POD process wear-resistant plastic coating applied to the keyboard is characterized by: Including UV primer, PU mid-coat, UV topcoat; The UV primer comprises the following raw materials in parts by weight: Acrylic resin 5-8 parts, polyurethane resin 25-35 parts, active diluent 9-11 parts, dispersant 1-1.2 parts, solvent I 7.5-13 parts, solvent II 2.5-5 parts, pigment 13-15 parts, anti-settling agent 2-3 parts, adhesion promoter 1-2 parts, filler 8-10 parts, matting powder 2.5-5.5 parts, photoinitiator 2.5-3 parts; The PU mid-coat comprises the following raw materials in parts by weight: Polyurethane resin 55-65 parts, dispersant 2-5 parts, solvent II 15-22 parts, pigment 3-5 parts, anti-settling agent 2-3 parts, wetting agent 0.2-0.3 parts, matting powder 4-5 parts; The UV topcoat comprises the following raw materials in parts by weight: 30-35 parts of UV polyurethane resin, 3-4 parts of acrylic resin, 6-8 parts of UV active diluent, 2.5-3 parts of photoinitiator, 3-5 parts of glass powder, 3.5-5 parts of solvent I; 6-10 parts of solvent II, 0.5-1 part of wetting agent, 0.5-1 part of leveling agent, 5-10 parts of anti-settling agent, 3-5 parts of wax powder, 1-5 parts of matting powder, and 15-20 parts of wax slurry.

2. The POD process wear-resistant plastic coating according to claim 1, characterized in that: The UV primer is a UV white primer; the PU intermediate paint is a PU black intermediate paint; and the UV topcoat is a UV matte topcoat.

3. The POD process wear-resistant plastic coating according to claim 1, characterized in that: In the UV primer, the acrylic resin includes Rohm and Haas A-11; the UV polyurethane resin consists of Changxing Chemical's 6145-100 and 6215-100, and the mass ratio of Changxing Chemical's 6145-100 to 6215-100 is 1.5-3:1; And / or, the active diluent is a UV active diluent; preferably, the UV active diluent consists of EM265 and EM221 of Changxing Chemical, and the mass ratio of EM265 to EM221 of Changxing Chemical is 2-4:

1.

4. The POD process wear-resistant plastic coating according to claim 1, characterized in that: In the UV primer, the dispersant includes EFKA-4310 from Eka; the solvent I includes methyl isobutyl ketone; the solvent II includes butyl acetate; the white pigment includes R902 from DuPont Chemical of the United States; the anti-settling agent includes NS-5500 from Disbaron; the adhesion promoter includes LTW from Germany's Sa; the filler includes talcum powder, and the matting powder includes E-1011 from Japan's Toso Co., Ltd.; the photoinitiator includes photoinitiator 184 and photoinitiator TPO.

5. The POD process wear-resistant plastic coating according to claim 1, characterized in that: In the PU mid-coat, the polyurethane resin includes ESB-1205 from Dongsheng Chemical Company.

6. The POD process wear-resistant plastic coating according to claim 1, characterized in that: In the PU mid-coat, the dispersant includes EFKA-4310; The solvent II comprises butyl acetate; The curing agent includes a mixture of HDI curing agent and butyl acetate, the mass ratio of the HDI curing agent to butyl acetate is 75:25; the HDI curing agent includes Bayer's N3390; The pigment is a black pigment; preferably, the black pigment includes Olironate 6 carbon black; The wetting agent includes BYK-358N from BYK; The matting powder includes E-1011 from Japan Toso Co., Ltd.

7. The POD process wear-resistant plastic coating according to claim 1, characterized in that: In the UV topcoat, the UV polyurethane resin includes 6145-100 from Changxing Chemical Company, 6071 from Changxing Chemical Company and L-6901 from Lancolu; the acrylic resin includes A-11 from Rohm and Haas; the UV active diluent includes EM265 from Changxing Chemical; and the photoinitiator includes photoinitiator 184 and TPO.

8. The POD process wear-resistant plastic coating according to claim 1, characterized in that: In the UV topcoat, the glass powder includes VX-SP of Japan Ronson Corporation; the solvent I includes methyl isobutyl ketone; the solvent II includes butyl acetate; the wetting agent includes BYK-358N of BYK; the leveling agent includes BYK-333 of BYK; the anti-settling agent includes NS-5500 of Disbaron; the wax powder includes Lanco TF1792 of Lubrizol Corporation; the matting powder includes E-1011 of Japan Toso Corporation; and the wax slurry includes ZJ-22 of Japan Gifu Corporation.

9. A method for preparing a wear-resistant plastic coating using the POD process according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1: Prepare UV primer, prepare each raw material according to the weight proportion of each raw material in UV primer, S1-1: Take 5-7.2 parts of solvent I, add 5-8 parts of acrylic resin while stirring at 300-500 rpm / min, then stir at 600-800 rpm / min to dissolve, add the remaining solvent I, and stir at 300-500 rpm / min for 10-15 minutes to obtain a semi-finished product 1-1; the fineness of the semi-finished product 1-1 is ≤10 μm; S1-2: 1-2.5 parts of solvent II, 1-1.2 parts of dispersant, and 5 parts of the semi-finished product 1-1 prepared in step S1-1 are mixed, and stirred at 300-500 rpm / min for 10-15 min; 13-15 parts of pigment are added, and stirred at 600-800 rpm / min until uniform, and then ground to a fineness of ≤20 μm, and then the remaining solvent II is added, and stirred at 300-500 rpm / min for 10-15 min to obtain a semi-finished product 1-2; the fineness of the semi-finished product 1-2 is ≤20 μm; S1-3: the remaining portions of the semi-finished product 1-1 of step S1-1, the semi-finished product 1-2 of step S1-2, 25-35 parts of polyurethane resin, and 9-11 parts of reactive diluent are mixed, and stirred at 300-500 rpm / min for 10-15 min, and then 8-10 parts of filler and 2.5-5.5 parts of matting powder are added in sequence, and stirred at 600-800 rpm / min for 20-30 min, and then 2.5-3 parts of photoinitiator, 2-3 parts of anti-settling agent, and 1-2 parts of adhesion promoter are added, and stirred at 500-600 rpm / min for 10-15 min to obtain a UV primer; S2: Prepare PU mid-coat, prepare each raw material according to the weight proportion of each raw material in PU mid-coat, S2-1: 11-13 parts of solvent II, 2-5 parts of dispersant, and 8-10 parts of polyurethane resin are mixed, stirred at 300-500 rpm / min for 10-15 min, 3-5 parts of pigment are added, and the mixture is stirred at 600-800 rpm / min until uniformly mixed, and then ground to a fineness of ≤20 μm, 2-3 parts of solvent II are added, and the mixture is stirred at 300-500 rpm / min for 10-15 min to obtain a semi-finished product 2-1, wherein the fineness of the semi-finished product 2-1 is ≤20 μm; S2-2: adding the remaining polyurethane resin to the semi-finished product 2-1 prepared in step S2-1, stirring at 300-500 rpm / min for 10-15 min, adding 4-5 parts of matting powder, stirring at 600-800 rpm / min for 20-30 min, adding 0.2-0.3 parts of wetting agent, 2-3 parts of anti-settling agent, and the remaining solvent II, and stirring at 300-500 rpm / min for 10-15 min to obtain PU intermediate paint; S3: Prepare UV topcoat, prepare each raw material according to the weight proportion of each raw material in the UV topcoat, S3-1: Add 3-4 parts of solvent I to 3-4 parts of acrylic resin while stirring at 300-500 rpm / min, then stir at 600-800 rpm / min to dissolve, add the remaining solvent I, stir at 300-500 rpm / min for 10-15 minutes to obtain a semi-finished product 3-1, wherein the fineness of the semi-finished product 3-1 is ≤10 μm; S3-2: 4-5.5 parts of solvent II, 30-35 parts of UV polyurethane resin, 6-8 parts of UV active diluent, and the semi-finished product 3-1 of step S1 are mixed, and stirred at 300-500rpm / min for 10-15min, and then 3-5 parts of glass powder, 3-5 parts of wax powder, and 1-5 parts of matting powder are added in sequence, and stirred at 600-800rpm / min for 20-30min, and then 2.5-3 parts of photoinitiator, 0.5-1 part of wetting agent, 0.5-1 part of leveling agent, 5-10 parts of anti-settling agent, 15-20 parts of wax slurry, and the remaining solvent II are added in sequence, and stirred at 300-500rpm / min for 10-15min to obtain a UV topcoat, wherein the fineness of the UV topcoat is ≤15μm.

10. An application of the wear-resistant plastic coating made by the POD process according to any one of claims 1 to 8 or the coating prepared by the preparation method according to claim 9, characterized in that: The coating is used to prepare a laser engraving coating on a keyboard, and a laser engraving product is obtained by laser engraving on the coating; The method of application is: (1) Prepare primer coating A, midcoat coating B, and topcoat coating C respectively; (2) coating the primer coating A of step (1) on the surface of the substrate, drying it, UV curing it, and cooling it to obtain a product containing a primer coating; (3) coating the surface of the product in step (2) with the intermediate coating B in step (1), drying, and cooling to obtain a product containing a primer coating and an intermediate coating; (4) continuing to coat the surface of the product in step (3) with the topcoat coating C in step (1), drying, UV curing, and cooling to obtain a product containing a primer coating, a midcoat coating, and a topcoat coating; (5) performing laser engraving on the product of step (4) to obtain a laser engraved product; In step (1), the coating A is obtained by mixing and stirring the UV primer, curing agent and diluent, and filtering; preferably, the mass ratio of the UV primer, curing agent and diluent is 100:5:70-90; And / or, the coating B is obtained by mixing and stirring the PU intermediate paint, curing agent and diluent, and filtering; the mass ratio of the PU intermediate paint, curing agent and diluent is 100:10:90-110; And / or, the coating C is obtained by mixing and stirring the UV coating and a diluent, and filtering; the mass ratio of the UV coating to the diluent is 100:60-80.